ChemInform Abstract: Resveratrol‐Based Benzoselenophenes with an Enhanced Antioxidant and Chain Breaking Capacity. Issue 39 (September 2015) - Tanini, Damiano; Panzella, Lucia; Amorati, Riccardo; Capperucci, Antonella; Pizzo, Elio; Napolitano, Alessandra; Menichetti, Stefano; d'Ischia, Marco
Abstract A novel class of resveratrol derivatives is obtained in good yields by direct selenenylation of resveratrol with Se(0) and SO2Cl2 in dry THF.